2015
DOI: 10.1111/resp.12687
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treatment with inhaled corticosteroid on serum periostin levels in asthma

Abstract: Background and objective: Periostin is a biomarker of eosinophilic airway inflammation and may contribute to airway remodeling in asthma. The antiinflammatory activity of inhaled corticosteroids (ICS) for asthma control is widely recognized. The aim of this study was to assess the effects of ICS on serum periostin levels and its relationships to inflammation and airway geometry. Methods: Forty-two healthy controls and 20 patients with steroid-naïve asthma before and after treatment with fluticasone propionate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…35 Nuijsink et al also found a negative correlation between U-EDN levels and FEV 1 , but could not find any relation to other symptoms. 32 In previous studies, periostin has been linked to decreased lung function 33 and eosinophil inflammation, 41 however, not to severity of disease. Elevated FeNO levels have been related to faster lung function decline in difficult-to-treat asthma.…”
Section: Discussionmentioning
confidence: 95%
“…35 Nuijsink et al also found a negative correlation between U-EDN levels and FEV 1 , but could not find any relation to other symptoms. 32 In previous studies, periostin has been linked to decreased lung function 33 and eosinophil inflammation, 41 however, not to severity of disease. Elevated FeNO levels have been related to faster lung function decline in difficult-to-treat asthma.…”
Section: Discussionmentioning
confidence: 95%
“…Other studies have found no differences between eosinophilic and noneosinophilic airway inflammation in terms of serum levels of periostin [41]. Some published studies have also concluded that adult patients with high levels of periostin show a better response to treatment with inhaled corticosteroids [42], omalizumab [44], or lebrikizumab (anti-IL-13) [44], suggesting that periostin is linked to increased inflammatory or immunological activity.…”
Section: Discussionmentioning
confidence: 98%
“…IL‐13 stimulates mucin secretion and clinical studies suggest that periostin and IL‐13 are increased in severe asthma . Also, the goblet cell appears to be an immune effector cell .…”
Section: Introductionmentioning
confidence: 99%